Core Addiction Medicine Competencies for Doctors: An International Consultation on Training. Issue 4 (October 2017) - Ayu, Astri Parawita; el-Guebaly, Nady; Schellekens, Arnt; De Jong, Cor; Welle-Strand, Gabrielle; Small, William; Wood, Evan; Cullen, Walter; Klimas, Jan
Background: Despite the high prevalence of substance use disorders, associated comorbidities, and the evidence base upon which to base clinical practice, most health systems have not invested in standardized training of health care providers in addiction medicine. As a result, people with substance use disorders often receive inadequate care, at the cost of quality of life and enormous direct health care costs and indirect societal costs. Therefore, this study was undertaken to assess the views of international scholars, representing different countries, on the core set of addiction medicine competencies that need to be covered in medical education. Methods: A total of 13 members of the International Society of 20 Addiction Medicine (ISAM), from 12 different countries (37% response rate), were interviewed over Skype, e-mail survey, or in person at the annual conference. Content analysis was used to analyze interview transcripts, using constant comparison methodology. Results: We identified recommendations related to the core set of the addiction medicine competencies at 3 educational levels: (i) undergraduate, (ii) postgraduate, and (iii) continued medical education (CME). The participants described broad ideas, such as knowledge/skills/attitudes towards addiction to be obtained at undergraduate level, or knowledge of addiction treatment to be acquired at graduate level, as well as specific recommendations, including the need to tailor curriculum to national settings and different specialties. Conclusions: Although it is unclear whether a global curriculum is needed, a consensus on a core set of principles for progression of knowledge, attitudes, and skills in addiction medicine to be developed at each educational level amongst medical graduates would likely have substantial value.